TANGGAPAN MASYARAKAT TERHADAP DAMPAK PANDEMI COVID - 19 TERHADAP EKONOMI NEGARA BERKEMBANG (INDONESIA) - ZAHRINA GHAISANY PULUNGAN; KHAIRINA TAMBUNAN (JURNAL ILMIAH MAKSITEK, 2021)
The Covid-19 pandemic that occurred in Indonesia since mid-2020 is very attention-grabbing. The impact is not only onpublic health, but also affects the country's economy. Even today the world economy is experiencing severe pressurecaused by the virus. The purpose of this study is to find out the public's response to the impact of pandemics on economiesin developing countries, especially in Indonesia. The research method used is a qualitative method by sharing openquestionnaires through google form. The sample population of 30 people consists of people with various work backgrounds.Many communities whose economies were negatively affected during the pandemic. From the results of the study found thatthe majority of respondents to the economy were negatively affected, namely as much as 56%, those who were positivelyaffected by 20% and those who were not affected by 24%. The economic impact is also felt by their surrounding environmentand the economy in Indonesia as a developing country, various government policies in addressing economic problems areneeded. In addition, community cooperation is also needed to overcome each other's problems.